Empowering Village Economies: Strategies for Leading Product-Based Development in Kudus Regency - Avi Budi Setiawan; Mochammad Yusuf (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
The development of villages based on leading product potential is crucial for optimizing local resources and fostering sustainable economic growth, particularly in Kudus Regency, which is a prominent manufacturing industry agglomeration in Indonesia. This study aims to map regional leading products at the village level and formulate development strategies based on empirical commodity clustering approaches. The study employs a qualitative research design incorporating focus group discussions (FGD), questionnaires, with participatory approach, conducted in stages with 200 key informants, including government officials, community leaders, and business actors. The findings reveal that phased strategies and product clustering are effective in enhancing village competitiveness and addressing socio-economic disparities. Specifically, the identification of leading products and their integration into development plans, supported by diversified processing and integrated marketing strategies, significantly improve economic resilience. The study recommends that policymakers facilitate participatory planning, invest in infrastructure and market access, and promote technological innovation to maximize the impact of village development initiatives. These findings underline the importance of aligning village potentials with regional and national strategies to achieve holistic and sustainable growth.